Effects of Autohemotherapy on Hematologic Parameters and Morphology of Canine Oral Papillomatosis - Borges, Olivia Maria Moreira; Araújo, Cynthia Larissa Medeiros; Ramalho, Gisele Cândida; da Silva, Rosangela Maria Nunes; Tanikawa, Atticcus; de Souza, Almir Pereira (Acta Scientiae Veterinariae, 2017)
Background: Several treatments for oral papillomatosis in dogs, with satisfactory results, have already been described in the literature. However, there is need for further studies regarding remission time, association and exposure to drugs, side effects, cost-effectiveness and reproducibility of results. Autohemotherapy (AHT) is a therapeutic technique increasingly used in veterinary medicine that has been providing satisfactory clinical results to treat several pathologies. The procedure consists of removing blood by intravenous puncture that is immediately re-administered via intramuscular, subcutaneous, intravenous or intradermal. Although the empirical isolated use via intramuscular reached excellent results in routine medical treatment of dogs and since few studies and protocols have been described for this species, many times the treatment is based on the experience with the bovine papillomatosis. To this end, this report describes a case of canine oral papillomatosis treated with autohemotherapy (AHT), emphasizing the dosage and clinical evolution of the case. Case: A one-year-old mongrel dog rescued from the street eight months earlier was treated. The animal was thin resulting from the small food amount ingested due to feeding difficulty, infested with ticks, had bad breath and few small warts on the lips, which, after five months, grew and multiplied, and were distributed throughout the oral cavity. The animal clinical history led to papillomatosis diagnosis, which was confirmed by cytological and histopathological exams. The AHT treatment consisted of taking 5 mL of whole blood without EDTA and immediately injecting this volume intramuscularly, every four days until the total remission of the clinical symptoms. Every four days, the papilloma fall off, and involution processes were recorded through a detailed macroscopic analysis of the warts (quantity, consistency, color and size), as well as hematological evaluations (blood count, hemoparasite screening and total plasm protein), which were performed before each AHT treatment until the complete clinical resolution of the disease (24 days). Discussion: The dose adopted in this autohemotherapy study was clinically effective since the papillomas started to fall off after four days of therapy, with total resolution in 24 days. Therefore, it can be concluded that the 5 mL AHT injected intramuscularly every four days reduced treatment time and decreased therapeutic costs. There are few studies evaluating more accurately the hematological aspects related to the therapeutic use of autohemotherapy to treat canine oral papillomatosis, the existing reports are restricted to the initial measurement as an evaluation of the general condition of the patient and/or diagnosis of possible basal diseases. In this study, no changes were observed in the blood count during the entire therapeutic process, demonstrating that the AHT did not interfere in the red series dynamics of the treated animal. Additionally, thrombocytosis followed by thrombocytopenia exhibited a correlation with the macroscopic appearance of warts [enlargement and modified color, texture, shape and consistency]. This observation is possibly related to a platelet mobilization toward the site of action [warts], so that there was a modulation in the immune response, amplifying the inflammatory process and tissue repair, which resulted in the fall off and involution of the papillomas.